Community awareness initiative about antimicrobial resistance: An educational intervention by medical undergraduates - Bhagyashri D. Rajopadhye; Vasundhara A. Londhe; Nivedita A. Pingle; Priti P. Dhande (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Antimicrobial resistance (AMR) is a global problem and an important consequence of inappropriate use of antimicrobial agents (AMAs). Studies have observed that a lack of awareness of AMR among healthcare professionals as well as consumers results in the irrational use of AMAs, a significant driver of AMR. MATERIALS AND METHODS: This educational intervention study was undertaken to assess community awareness regarding AMAs and AMR and to educate them. Ten volunteer students from II MBBS were made aware of AMR, its impact and measures to reduce resistance through a lecture by Pharmacology faculty. Students interacted with 220 family representatives in the community to assess their knowledge about AMAs and AMR using a 15-item pre-validated questionnaire. Charts, videos, and role-play were used to impart knowledge about the rational use of AMAs, AMR, and its consequences. Participants' understanding was ensured with feedback taken on Lickert scale. RESULTS: Students interacted with the study participants and found that most were aware of the term 'antibiotic' (90.8%), but 67% were clueless regarding antibiotic resistance. The purpose of AMA use was not adequately known to 43% as they mentioned using these for diarrhea, viral fever, cough, cold, and sore throat. AMAs were purchased by 40% of participants as OTC medicine, whereas Azithromycin and Amoxicillin were the AMAs they could remember by name. The reasons for buying OTC antibiotics were the inconvenience of doctors' clinic timings, unaffordable consultation charges, and easy antibiotic availability. Students also learned about communication etiquette during this community interaction. This educational intervention proved helpful as the participants agreed that the unnecessary use of AMAs makes them ineffective and AMR is preventable by simple measures. CONCLUSION: A multifactorial approach involving prescribers, regulatory Government authorities and general public is needed to control irrational use of antimicrobials. Timely interventions are necessary to increase the awareness of AMR in the community.